American Public Support for U.S. Military Operations from Mogadishu to Baghdad - Larson, Eric V. (RAND Corporation, 2005)
The support of the American public is widely held to be a critical prerequisite for undertaking military action abroad. This monograph describes American public opinion toward wars and other large military operations over the last decade, to delineate the sources of support and opposition for each war or operation, to identify the principal fault lines in support, and to illuminate those factors that are consistent predictors of support for and opposition to military operations.